2015
DOI: 10.1038/srep18635
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of the synergistic effects of warming and invasive algae on a temperate reef-builder coral

Abstract: In the current global climate change scenario, stressors overlap in space and time, and knowledge on the effects of their interaction is highly needed to understand and predict the response and resilience of organisms. Corals, among many other benthic organisms, are affected by an increasing number of global change-related stressors including warming and invasive species. In this study, the cumulative effects between warming and invasive algae were experimentally assessed on the temperate reef-builder coral Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…Exploring species-specific thermal sensitivities among different components of benthic communities is, therefore, a key step toward forecasting the future composition and functionality of these communities in the face of climate change. However, while important efforts in this direction have been taken in shallow tropical reefs, thermotolerance analyses in temperate benthic communities largely lag behind (Kersting et al, 2015;Linares, Cebrian, Kipson, & Garrabou, 2013;Savva, Bennett, Roca, Jordà, & Marbà, 2018;Torrents, Tambuté, Caminiti, & Garrabou, 2008).…”
mentioning
confidence: 99%
“…Exploring species-specific thermal sensitivities among different components of benthic communities is, therefore, a key step toward forecasting the future composition and functionality of these communities in the face of climate change. However, while important efforts in this direction have been taken in shallow tropical reefs, thermotolerance analyses in temperate benthic communities largely lag behind (Kersting et al, 2015;Linares, Cebrian, Kipson, & Garrabou, 2013;Savva, Bennett, Roca, Jordà, & Marbà, 2018;Torrents, Tambuté, Caminiti, & Garrabou, 2008).…”
mentioning
confidence: 99%
“…Recently, these results were contrasted by a study which demonstrated that long‐term exposure of C. caespitosa to thermal stress (29°C) resulted in no impact on tissue necrosis or photosynthetic efficiency (Kersting et al. ). However, exposure to temperature stress in addition to the presence of invasive algae negatively impacted photosynthetic efficiency and caused tissue necrosis in the coral (Kersting et al.…”
Section: Introductionmentioning
confidence: 96%
“…However, exposure to temperature stress in addition to the presence of invasive algae negatively impacted photosynthetic efficiency and caused tissue necrosis in the coral (Kersting et al. ). Another study found that for two temperate coral species ( C. caespitosa and Oculina patagonica ), short‐term thermal stress up to 5°C above the mean summer temperature resulted in no change in symbiont density (Rodolfo‐Metalpa et al.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1999, this coral was exposed to several mass mortalities due to the warming events (Garrabou et al, 2009; Jiménez et al, 2014; Kersting et al, 2013a; Kružić et al, 2013; Perez et al, 2000; Rodolfo-Metalpa et al, 2005) and declined to 55% in some parts of the Mediterranean Sea (Casado-Amezúa et al, 2015). In addition to warming events, competition with invasive algae likely contributed to the mortality of this coral species (Kersting et al, 2015). Invasive algae were observed in different regions of Mediterranean Sea where living C. caespitosa are present (Kersting et al, 2014a; Kružić et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2) (Casado-Amezúa et al, 2011; Casado-Amezúa et al, 2014; Kersting, 2013; Kersting et al, 2013a; Kersting et al, 2013b; Kersting et al, 2014a; Kersting et al, 2014b; Kersting et al, 2015; Kersting et al, 2016; Kružić and Benkovic, 2008; Kružić and Požar-Domac, 2003; Kružić and Požar-Domac, 2007; Kružić et al, 2012; Kružić et al, 2013). Some colonies in the Eastern part of the Adriatic Sea are particularly threatened by anthropogenic activities such as e.g., tuna farming (Kružić and Požar-Domac, 2007).…”
Section: Introductionmentioning
confidence: 99%